Історія кріофізики в Україні - Овчаренко, Юлія Сергіївна (ФОП Панов А. М., 2019)
У монографії методом історико-наукового аналізу на основі введення раніше недоступних архівних джерел висвітлено основні етапи еволюції науково-організаційних основ кріофізики в Україні. Вперше в історичній науці розроблено її періодизацію. У роботі реконструйовано процес інституціоналізації науково-дослідної роботи з напряму низькотемпературної фізики. Розкрито й доведено вагомий внесок наукових шкіл, що працювали у галузі кріофізики. Автором представлено найвагоміші результати науково-дослідних робіт творчих колективів, що були інтегровані в національну промисловість. Книга розрахована на широке коло спеціалістів – фізиків, інженерно-технічних працівників, а також всіх хто цікавиться історією вітчизняної науки.

In the monograph by the method of historical and scientific analysis on the basis of the introduction of previously inaccessible archival sources the main stages of the science evolution and organizational foundations of cryophysics in Ukraine was illustrated. For the first time in historical science the periodization was developed. In the scientific work, the process of institutionalization of research work in the field of low-temperature physics, was reconstructed. The significant contribution of scientific schools that worked in the field of cryophysics, was discovered and proved. The most important results of scientific research works of creative groups that were integrated into the national industry were presented by the author. The book is designed for a wide range of specialists – physicists, engineering and technical workers, as well as all those who are interested in the history of science.
History of cryophysics in Ukraine
Keywords: фізика низьких температур; спектроскопія; молекулярні кристали; кріомедицина; наукові дослідження; cryophysics in Ukraine; low-temperature physics; process of institutionalization; scientific schools; molecular crystals